Evaluation of pore size distribution and permeability reduction behavior in pervious concrete. (5th July 2021) - Huang, Jiandong; Zhang, Yi; Sun, Yuantian; Ren, Jiaolong; Zhao, Zedong; Zhang, Junfei
Highlights: Evaluation of the thickness effects on the pervious concrete. Clogging behavior of pervious concrete. Characterization of the pore size distribution in pervious concrete. Modeling of clogging behavior considering the pore size distribution. Abstract: Pervious concrete is an environmentally friendly material that improves water permeability, skid resistance, and sound absorption characteristics. However, due to a large number of pores and the absorption capacity, pervious concrete faces the problem of clogging caused by dust particles and solid contaminants entering the internal pores. In this study, both pore size distributions (PSD) of the pervious concrete and permeability reduction behavior are studied by laboratory tests. The extent of permeability reduction is addressed by designing the penetration test for 21 groups of pervious concrete mixes with varying aggregate gradations and specimen thickness. The PSD is determined by the two-dimensional (2D) sliced image scanned by the Computed Tomography (CT). An approach to represent the characteristic pore size of pervious concrete is proposed and verified. Results showed that: the effect of thickness on permeability is negligible while on clogging behavior is significant. The ratio between the clogging sand sizes and the characteristic pore size is an important parameter that affects the clogging behavior and can be used to predict the anti-clogging performance.